TIME SAVING STRATEGIES IN SIMULTANEOUS INTERPRETING - Sevinch Azimova Nizomjon qizi (Journal of new century innovations, 2024)
Annotation. This article explores time-saving strategies in simultaneous interpreting, aiming to enhance the efficiency and effectiveness of the process. Through a comprehensive analysis of existing literature, this study identifies key areas for improvement and proposes practical methods to streamline the translation workflow. The results highlight the significance of these strategies in achieving optimal time management and maintaining high translation quality.